2022
DOI: 10.3390/cancers14143455
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 as a Potential Biomarker of Prognosis and Invasive-Related Parameters in Liver and Colorectal Cancer: A Systematic Review and Meta-Analysis of Human Studies

Abstract: Neuropilin-1 (NRP1) is a transmembrane protein involved in numerous cellular functions which has had increasing interest from cancer researchers. Liver cancer and colorectal cancer (CRC) are two of the most frequent and deadly tumors with a complex pharmacological framework. Here, we assessed the prognostic, diagnostic and clinicopathological value of NRP1 in liver cancer and CRC patients. We searched PubMed, Scopus, Web of Science, Embase and Cochrane Library databases for articles evaluating the NRP1 correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…40 Additionally, a systematic review indicated that NRP1 is a potentially useful biomarker for HCC, and that its overexpression is significantly related to both disease development and lower survival rates, as well as an elevated risk of vascular invasion and metastasis. 41 Flavia et al verified the substantial link between the high expression of FOXO3 and the risk of invasion as a novel biomarker in HCC, as well as its diagnostic and prognostic utility in another review encompassing 1059 HCC cases. 42 In an HCC investigation, researchers also developed an immune-related model made up of 11 genes, which can both identify prognostic stratification and offer a fresh viewpoint for the search for immunotherapeutic medicines.…”
Section: Discussionmentioning
confidence: 97%
“…40 Additionally, a systematic review indicated that NRP1 is a potentially useful biomarker for HCC, and that its overexpression is significantly related to both disease development and lower survival rates, as well as an elevated risk of vascular invasion and metastasis. 41 Flavia et al verified the substantial link between the high expression of FOXO3 and the risk of invasion as a novel biomarker in HCC, as well as its diagnostic and prognostic utility in another review encompassing 1059 HCC cases. 42 In an HCC investigation, researchers also developed an immune-related model made up of 11 genes, which can both identify prognostic stratification and offer a fresh viewpoint for the search for immunotherapeutic medicines.…”
Section: Discussionmentioning
confidence: 97%
“…NRP-1 has been overexpressed in various cancer types, including lung, breast, pancreatic, and prostate cancers. NRP-1 affects cell survival, migration, and attraction by binding to ligands and various co-receptors and may serve as a cancer biomarker of refractory tumors ( 25 ).…”
Section: Nrp Signalingmentioning
confidence: 99%
“…The identification of useful biomarkers is one of the main objectives to increase the rate of early diagnosis in the HCC landscape 8 . In this line, several investigations have found an overexpression of NRP1 in the tumor tissue of patients diagnosed with HCC compared to the healthy liver tissue [76][77][78][79][80][81][82][83][84][85] . Similar results were also described in preclinical studies, showing increased NRP1 levels in different HCC cell lines with respect to the normal liver L02 cell line 85,86 .…”
Section: Nrp1 As a Biomarkermentioning
confidence: 96%
“…Similar results were also described in preclinical studies, showing increased NRP1 levels in different HCC cell lines with respect to the normal liver L02 cell line 85,86 . Although fewer investigations have analyzed the potential use of NRP1 as serum biomarker, positive findings have been also published 79,87 , highlighting the potential role of this NRP receptor in the diagnostic field of HCC [76][77][78][79][80][81][82][83][84][85][86][87] .…”
Section: Nrp1 As a Biomarkermentioning
confidence: 99%
See 1 more Smart Citation